Hybrid raman-erbium random fiber laser - Zainol Abidin, Nadiah Husseini (2017)
In random distributed feedback fiber laser (RDB-FL), Rayleigh scattering (RS) is utilized as random feedback mechanism in the lasing cavity. Random feedback mechanism works by scattering the propagating light; increasing the path of the light. Once optical gain exceeds total intracavity loss, random lasing is commenced. Owing to the weak, long, and continuous random scattering centers, the cavity length of the laser is boundless; allowing cavity length to be varied accordingly. Despite the outstanding traits of RDB-FL, it requires a high amount of power to achieve threshold. In this research, an enhanced hybrid configuration of the RDB-FL based on the integration of 80 km of single mode fiber (SMF) and erbium-doped fiber (EDF) in an open-ended linear cavity is proposed. The laser is powered by a single 1455 nm Raman pump through the ends of the laser cavity. The proposed architecture is named as hybrid erbium random fiber laser (HRFL) based on its fundamental operation; the hybrid amplification of Raman and EDF gain assisted by RS feedback. The HRFL utilizes the same pump source to initiate stimulated Raman scattering (SRS) and excite the erbium ions. The Stokes signal produced by SRS then acts as a signal to the EDF. A conventional RDB-FL is first designed and developed to determine the optimum pumping scheme and range of cavity length that can cater for SMFs with different Raman gain coefficients. Two types of SMF are tested, which are SMF-28e fiber and TrueWave REACH single mode fiber (TW). It was found that cavity length of 77-91 km and inward pumping scheme are the optimum conditions to achieve high slope efficiency and low threshold. EDF is then integrated to the developed configuration to construct the HRFL. The length of EDF is also varied to observe the spectral and power performance.The HRFL output is stable lasing peak at wavelength 1555-1565 nm with 38 % slope efficiency and 260 mW threshold power. Intriguingly, it is discovered that by using an appropriate EDF length, dual lasing peak can be obtained without the aid of any reflectors/filters. The HRFL not only managed to amplify the 2nd Raman gain peak (1565 nm), but also the 3rd Raman gain peak (1595 nm), producing a dual peak laser in between the C-band and the L-band. To minimize the high disparity between the dual peaks, the HRFL is enhanced by modifying the architecture. Balanced dual peaks with peak discrepancy of 0.16 dB is achieved at maximum peak power of -10.66 dBm. The advantage of the HRFL is the dispensable need for a unique pump wavelength, compared to other HRFLs employing EDF that have used separate pumps to power the SMF and EDF. The proposed configuration also has a lower threshold condition by a factor of 5 compared to HRFLs utilizing SRS and higher power conversion efficiency compared to other HRFLs employing EDF. It is believed that the novelty of this research work lies within the use of a simple open-ended cavity design to produce single and dual peak lasing.